Characterization of chlorophyll based dye-sensitized solar cell using general-purpose photovoltaic device model - Wan Nur Ainna Amirah, Wan Zulkifli; Nik Fatin Qistina, Amran; Norazila, Jaalam; Faiz, Arith; Ahmad Syahiman, Mohd Shah; Ali, Khumaeni (Semarak Ilmu Publishing, 2024)
In dye-sensitized solar cells (DSSCs), light is absorbed by the sensitized dye. When light strikes the dye molecule, it absorbs photons and becomes excited to a higher energy state. This excited state allows the dye molecule to inject an electron into the conduction band of the semiconductor, generating an electric current. The selection of dye properties is very significant, as it can help to improve the performance of DSSCs. However, achieving an identical output current-voltage characteristic from the same batch of plants or fruits used as dyes is very difficult. Furthermore, improving the electrical performance, such as short-circuit current density and efficiency, of fabricated dye-sensitized solar cells is critical, as many experimental factors need to be considered. Therefore, to minimize the extra use of material resources due to the risk of unsuccessful fabrications and to obtain better performance ideally, conducting simulation-based studies is important to optimize the performance of DSSCs. The free software General-Purpose Photovoltaic Device Model (GPVDM) is a promising and interesting tool due to its free license and easy accessibility through a graphical interface for simulating optoelectronic devices, including OLEDs, OFETs, and various types of solar cells. This paper considers GPVDM, a 3-D photovoltaic device model, to simulate the proposed structure with different samples of chlorophyll dye for DSSC performance. The paper aims to characterize the high current density-voltage (J-V) of chlorophyll-based DSSCs and identify suitable photovoltaic simulation software for running simulations of chlorophyll-based DSSCs. Finally, the outcomes are compared with experimental data reported in various literature sources. The results show an enhanced short-circuit current density (Jsc) of 0.3556 mA cm-2 for Cordyline fruticose leaves (Chl E), which is the highest among the other dyes tested. The value of simulated short-circuit current density (Jsc) is slightly different from the experimented result Jsc reported in the published paper. In conclusion, GPVDM can be considered suitable for modeling DSSCs.